Il corpo del grattacielo - Panizza, Mario (Dialogoi. Rivista di studi comparatistici, 2020)
The “building-fabrica” includes, among its definitions, the compound expression of “body of the building”. The two words, combined in this way, add the idea of ​​organism to the concept of building. In a completely natural, lexical way, the physical description is completed with the character, generating a new value: the expression of the identity. In the architectural panorama there is an interpreter who prefers an isolated exhibition, showing in comparison with the others the physical and symbolic character: the skyscraper. The skyscraper identifies an extreme and paradoxical architecture, an expression of primacy, a different phenomenon, which inserts the value of quantity and symbolism into the categories of the judgment. The permanence of these characteristics makes him the character of a story that gets together several generations, mixes with several ethnic groups and meets the events and styles of individual architects.